2020
DOI: 10.3390/agronomy10121941
|View full text |Cite
|
Sign up to set email alerts
|

Acidified Animal Manure Products Combined with a Nitrification Inhibitor Can Serve as a Starter Fertilizer for Maize

Abstract: There is an urgent need for better management practices regarding livestock farm nutrient imbalances and for finding alternatives to the actual use of mineral fertilizers. Acidification of animal manure is a mitigation practice used to reduce ammonia emissions to the atmospheric environment during manure storage and land application. Acidification modifies manure physicochemical characteristics, among which soluble N and P significantly increase. The main objective of this study was to investigate if acidifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…However, Pantelopoulos et al (2017) found that thermal drying of solid phase digestate decreased phosphorus uptake in ryegrass plants compared with non-dried solid digestate. In another study, acidification of the solid fraction after screw press separation of digestate increased the water-extractable phosphorus content and also plant phosphorus uptake, but not plant biomass, in maize (Zea mays L.) compared with non-acidified solid digestate (Regueiro et al, 2020) (Table 4).…”
Section: Use Of Solid Phase Digestate Products As Phosphorus-rich Pla...mentioning
confidence: 97%
“…However, Pantelopoulos et al (2017) found that thermal drying of solid phase digestate decreased phosphorus uptake in ryegrass plants compared with non-dried solid digestate. In another study, acidification of the solid fraction after screw press separation of digestate increased the water-extractable phosphorus content and also plant phosphorus uptake, but not plant biomass, in maize (Zea mays L.) compared with non-acidified solid digestate (Regueiro et al, 2020) (Table 4).…”
Section: Use Of Solid Phase Digestate Products As Phosphorus-rich Pla...mentioning
confidence: 97%
“…has been widely studied [12], very little research has been conducted to investigate the starter effect of fertilizers permitted in organic farming. Moreover, the scarce information that currently exists derives mainly from summer crops [13,14], because the optimal soil temperature and water content (due to the irrigation) in late spring can easily accelerate the mineralization activity of the soil's microbial community [15]. On the contrary, low temperatures and high rainfall can cause a deficiency in the availability of soil nutrients, especially during the initial growth of winter crops under organic farming conditions [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…While an increasing number of published studies is dealing with trade-offs of slurry treatment and application techniques, thereby considering greenhouse gas fluxes, nitrate leaching (Maris et al 2021;Cameira et al 2019;Park et al 2018;Kayser et al 2015;Powell et al 2011) and productivity (Baral et al 2021;Regueiro et al 2020;Fangueiro et al 2017;Huijsmans et al 2016), very little is known on fertilizer N partitioning in the plant-soil-system and on full N balances of conventional slurry broadcast spreading compared to injection and acidification. This particularly applies for montane grasslands of the alpine region in Europe and still prevents a holistic assessment how these refined slurry application techniques affect the actual plant N uptake and fertilizer N stabilization in the soil, which is key to preserve soil fertility on the long term.…”
Section: Introductionmentioning
confidence: 99%